Geochemical criteria for identifying diamond-bearing areas - Krinochkin Lev; Kilipko Victor; Trofimov Alexander; Krinochkina Olga; Mamina Dinya (E3S Web of Conferences)
The paper demonstrates that diamondiferous objects may be pinpointed even by the middle-scale geochemical surveys. Relevant criteria were developed to identify and classify such objects by their prospectivity. The study materials are the results of geochemical surveys carried out in the Myunusyak area, Sakha-Yakutia, RF, in 2020-2022. The geochemical study was carried out by lithochemical sampling. Sampling was carried out on a scale of 1:200,000, i.e., the sampling interval varied between 1 and 1.5 km. The samples were analyzed by ICP-MS. The results of the study show the possibility of identifying potentially diamondiferous areas by geochemical methods identifying geochemical halos of kimberlite fields. The prerequisite for this was the idea of diamondiferous objects as areas of spatially close kimberlite bodies and associated host rock alterations. The products of their destruction form secondary halos and trains of indicator elements of kimberlite magmatism, which dimensions can significantly exceed the those of the pipes and are detectable by the medium-scale geochemical surveys. Using the criteria developed, produced an assessment of the diamond potential of the Myunyusyak area, Anabar Craton. A number of promising areas were identified by the authors, including one of especially high prospectivity.